PENGARUH KARAKTERISTIK USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI DENGAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABEL MODERATING - Ernawati, Dwi (Jurnal Ilmiah Akuntansi Indonesia, 2017)
Abstract: Accounting information needed by management to plan the company's activities in the future, especially at the stage of analyzing the consequences of each alternative measures used in decision-making, allowing choosing the best among alternative actions considered. The reality today is not a bit of Small and Medium Enterprises (SMEs) who do not understand, prepare or use of accounting information. Many factors affect the use of accounting information on SMEs one of which is the knowledge of accounting owner / manager and the age of the business. There are also environmental factors are not sure that can strengthen or weaken the influence of these factors. The purpose of this study was to analyze the influence of accounting knowledge and business life of the use of accounting information moderated by factors of environmental uncertainty. Population and sample in this penelirtian is SMEs who register their business at the Department of Trade and Industry Jember 2015. The sampling technique is simple random sampling method as many as 73 pieces. Data collection method is by distributing questionnaires to the respondents. The results show that knowledge of business accounting and age affect the use of accounting information, while environmental uncertainties not found moderating effect of accounting knowledge and business life of the use of accounting information.Keywords: Accounting Information, Environmental Uncertainty, SMEs,